O uso do microblog Twitter em sala de aula: perspectivas para o ensino da escrita no 9º ano do Ensino Fundamental - Prates, Tharsila Dantas (2014)
The present work is in the line of research Reading, writing and teaching of Portuguese. The theme is the use of the microblogging service Twitter for writing s activities to grade school students. The aim of this work is to propose activities using Twitter for Portuguese classes. The specific objectives are: describe the Twitter and propose writing s activities that permit a concise writing and that prepare the students to summarization of texts. The theoretical base is the research in Textual Linguistics at the social, cognitive and interactional perspective, used for define textual coherence (BEAUGRANDE & DRESSLER, 1981; BEAUGRANDE, 1997; KOCH & TRAVAGLIA, 2011, 2012); show the standards of textuality (BEAUGRANDE & DRESSLER, 1981; KOCH & TRAVAGLIA, 2011, 2012); the macrostructure or the principal idea of text (VAN DIJK, 2008) and the roles to reduce semantic information (VAN DIJK & KINTSCH, 1975). In the presence of access to new technologies and the need of teaching of concise and coherent writing, we developed a proposal with the use of Twitter to be applied to an opinion article sort of text worked by educators in nine year of grade school. We believe that microblogging can be an aid to the Portuguese teacher make students develop the power of synthesis and writing coherently